Using Grammarly to Identify Errors of Hospitality Students' in Writing - Anggayana, I Wayan Agus; Wartana, I Made Hedy (Akademi Komunitas MAPINDO, 2022)
This research simulates the use of Grammarly as one tool of an online assessment in identifying grammatical and mechanical errors of hospitality students' essays in writing English. The result analysis shows that Grammarly is used to assess the students' writing both grammatical and mechanical errors. From Grammarly report, it represents the quality of writing. Grammarly is an online proofreading service that checks for students' grammar, spelling, and punctuation errors. Grammarly automatically verifies or detects the work typed based on a variety of factors and reveals a variety of student writing errors, both in terms of grammatical and mechanical. This finding suggests that lecturer can use Grammarly as online automated software to implement corrective evaluation of Hospitality Students' writing. This research is descriptive qualitative research. Researchers classify the the issues in grammarly: (a) Correctness (b) Clarity, (c) Engagement, (d) Delivery, the data taken only for the female hospitality students. Based on results and discussion total Correctness 373, Clarity 8, Engagement 7, Delivery 2. Conslusion for this research, female hospitality students are having more errors in Correctness which is includes Improves spelling, grammar, and punctuation. Keywords: Identify Errors, Hospitality Students, Grammarly, Writing